Adolescents’ developing awareness of inequality: Racial and ethnic differences in trajectories - Wray‐Lake, Laura; Alvis, Lauren; Plummer, Jason A.; Shubert, Jennifer; Syvertsen, Amy K. (Child development, 2023)
To advance knowledge of critical consciousness development, this study examined age‐related change in awareness of inequality by race and ethnicity, gender, parent education, generation status, and their interactions. With longitudinal data (2013–2017) from 5019 adolescents in grades 6–12 (55.0% female) from California, Minnesota, and West Virginia, multigroup second‐order latent growth curves were estimated for Black (13.7%), Latinx (37.0%), Asian (8.1%), and white (41.3%) youth. Black, Latinx, and Asian adolescents increased awareness of inequality longitudinally; white youth showed no change. Multiracial youth accelerated awareness of inequality in mid‐adolescence; changes in race and ethnicity predicted decline, followed by increases. Girls with more educated, immigrant‐origin parents started out more aware of inequality. Results signal the need for race‐specific and intersectional approaches to studying critical consciousness development.